The terrorist attacks and the human live birth sex ratio: a systematic teview and meta-analysis - Masukume, Gwinyai; O'Neill, Sinéad M; Khashan, Ali S; Kenny, Louise C; Grech, Victor (Acta Medica, 2017)
AIM: The live birth sex ratio is defined as male/total births (M/F). Terrorist attacks have been associated with a transient decline in M/F 3-5 months later with an excess of male losses in ongoing pregnancies. The early 21st century is replete with religious/politically instigated attacks. This study estimated the pooled effect size between exposure to attacks and M/F. Registration number CRD42016041220. METHODS: PubMed and Scopus were searched for ecological studies that evaluated the relationship between terrorist attacks from 1/1/2000 to 16/6/2016 and M/F. An overall pooled odds ratio (OR) for the main outcome was generated using the generic inverse variance method. RESULTS: Five studies were included: 2011 Norway attacks; 2012 Sandy Hook Elementary School shooting; 2001 September 11 attacks; 2004 Madrid and 2005 London bombings. OR at 0.97 95% CI (0.94-1.00) (I2 = 63%) showed a small statistically significant 3% decline in the odds (p = 0.03) of having a male live birth 3-5 months later. For lone wolf attacks there was a 10% reduction, OR 0.90 95% CI (0.86-0.95) (p = 0.0001). CONCLUSION: Terrorist (especially lone wolf) attacks were significantly associated with reduced odds of having a live male birth. Pregnancy loss remains an important Public Health challenge. Systematic reviews and meta-analyses considering other calamities are warranted.
Keywords: Live Birth; narození živého dítěte; Sex Ratio; Pregnancy; těhotenství; Male; lidé; terorismus; mužské pohlaví; ženské pohlaví; Female; samovolný potrat; Abortion, Spontaneous; Humans; Terrorism; poměr pohlaví